2019
DOI: 10.1111/jcal.12383
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on Internet of things in education: Benefits and challenges

Abstract: With close to 20.4 billion devices connected to the Internet to be deployed by 2020, Internet of things (IoT) is already being leveraged in diverse sectors. Now, because of the ubiquitous nature of IoT devices, schools and academic institutions are looking to incorporate IoT in educational activities. With the increased use of IoT in the education domain, it is of utmost importance to study how this technology with its distinguished system functions such as sensing and decision making can support and challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 76 publications
2
91
0
3
Order By: Relevance
“… 10 Accordingly, students’ former experiences determines their familiarity with online learning modes, including the tools or platforms used for information transmission and interpersonal interaction. 11 Concerning students’ completion in higher online education, success predictors include learning strategies, academic self-efficacy, academic goals and intentions, institutional or college adjustment, employment, supportive network and faculty–student interaction. 12 13 Compared with students’ completion of online learning, students’ perceptions of online learning have received less attention.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Accordingly, students’ former experiences determines their familiarity with online learning modes, including the tools or platforms used for information transmission and interpersonal interaction. 11 Concerning students’ completion in higher online education, success predictors include learning strategies, academic self-efficacy, academic goals and intentions, institutional or college adjustment, employment, supportive network and faculty–student interaction. 12 13 Compared with students’ completion of online learning, students’ perceptions of online learning have received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Along with that, this research study is exclusive because, in a single study, the complete collection of the organizational variables, demographic variables, the opinion of teachers and students, the comparison of their descriptions and perceptions of the key factors of IoT in education has been taken into consideration. This literature review revealed major work gaps concerning IoT education and its branches, such as physical systems (Kassab et al 2019) [67]. These gaps are caused by a large number of everevolving technologies, highly diverse technology domains, various relevant standards, of IoT education's cross-disciplinary nature.…”
Section: Research Gapmentioning
confidence: 99%
“…The IoT permeates all areas of our daily life such as industry, energy, health, social life. Currently there is an increasing interest in internet of things and its role in educational systems (Kassab et al, 2019) which can facilitate education life and contribute to the effectiveness of educational practices (Uskov et al, 2016;Jeong et al, 2016;Songsom et al, 2019). The integration of the Internet of Things in education aims at building a smart environment through smart classrooms (Gligoric et al, 2012;El Mrabet et al, 2017), smart campuses, and smart school management systems (Vihervaara & Alapaholuoma, 2017).…”
Section: Introductionmentioning
confidence: 99%